Design and development of a test rig to investigate the load deflection characteristics of helical spring lock washers - Wagh, Hemant; Desale, Girish R. (International Journal of Structural Integrity, 2018)
Purpose The helical spring lock washer is a part of nut-bolt joint assembly used in different industries like automobile, aerospace, mechanical, chemical, electrical, electronics, etc. It works as a part of temporary joint and plays important role in loosening behavior of assembly under dynamic (vibrations) conditions. Thus, it is necessary to investigate the performance of helical spring lock washer under different controlled operating conditions in order to satisfy its functional requirement. Design/methodology/approach In the present investigation, a novel test rig is designed and developed to determine the load deflection characteristics of helical spring lock washers. The test rig facilitates the controlled linear displacement of the Helical Spring Lock (HSL) washer with predetermined angular rotation of the handle gives the corresponding reaction load on the display. Additionally, the repeatability and reproducibility of the test rig was carried out. Findings The newly designed and developed test rig is enough capable to differentiate the load deflection characteristics during compressive loading and unloading of helical spring lock washers. Additionally, the loss of strain energy can be determined from the load deflection characteristics of helical spring lock washer. Originality/value The present test rig is designed and developed to investigate the load deflection characteristics under compressive loading and unloading of Helical spring lock washer. The test rig has least count of 0.4905N for load measurement and 0.01389 mm for linear displacement.